Xenotransplantation of Porcine Islet Cells as a Potential Option for the Treatment of Type 1 Diabetes in the Future - Reichart, B.; Niemann, H.; Chavakis, T.; Denner, J.; Jaeckel, E.; Ludwig, B.; Marckmann, G.; Schnieke, A.; Schwinzer, R.; Seissler, J.; Tönjes, R. R.; Klymiuk, N.; Wolf, E.; Bornstein, S. R. (Hormone and Metabolic Research, 2015)
Solid organ and cell transplantation, including pancreatic islets constitute the treatment of choice for chronic terminal diseases. However, the clinical use of allogeneic transplantation is limited by the growing shortage of human organs. This has prompted us to initiate a unique multi-center and multi-team effort to promote translational research in xenotransplantation to bring xenotransplantation to the clinical setting. Supported by the German Research Foundation, an interdisciplinary group of surgeons, internal medicine doctors, diabetologists, material sciences experts, immunologists, cell biologists, virologists, veterinarians, and geneticists have established a collaborative research center (CRC) focusing on the biology of xenogeneic cell, tissue, and organ transplantation. A major strength of this consortium is the inclusion of members of the regulatory bodies, including the Paul-Ehrlich Institute (PEI), infection specialists from the Robert Koch Institute and PEI, veterinarians from the German Primate Center, and representatives of influential ethical and religious institutions. A major goal of this consortium is to promote islet xenotransplantation, based on the extensive expertise and experience of the existing clinical islet transplantation program. Besides comprehensive approaches to understand and prevent inflammation-mediated islet xenotransplant dysfunction [immediate blood-mediated inflammatory reaction (IBMIR)], we also take advantage of the availability of and experience with islet macroencapsulation, with the goal to improve graft survival and function. This consortium harbors a unique group of scientists with complementary expertise under a cohesive program aiming at developing new therapeutic approaches for islet replacement and solid organ xenotransplantation.
Keywords: diabetes mellitus type 1; xenotransplantation; islet cells